International and local students' satisfaction of healthcare services (Journal of Business Management and Accounting, 2011)
This research aims to measure the international and local students’ satisfaction toward university healthcare services provided by one public university. The study determines the students’ expectations, perceptions and the gap between them based on the five dimensions of service quality of a modified SERVQUAL instrument. A total of 273 respondents answered the questionnaires consisted of 134 international students and 139 local students. The study shows that both groups of students were generally not satisfi ed with the services provided by the healthcare center. Dissatisfaction among the International students was more closely related to the assurance-dimension; while the local students were dissatisfi ed with the reliability-dimension. Furthermore, the results show significant differences between the international and local students’ satisfaction with regard to assurance-dimension only.